Burning daylight - McIntire, Emily (McIntire, Emily. Defying the stars, 2025)
"Juliette Calloway lives in a world of luxury, legacies, and lies. The daughter of Rosebrook Falls' most powerful family, her life is a crafted performance, and she's tired of being polished to perfection. Roman Montgomery doesn't exist. Not officially, anyway He's a shadow, a hidden weapon, the secret heir to an empire soaked in danger and a generations-old feud. When their paths cross, sparks fly. No names. No pasts. Just reckless smiles and a chemistry neither of them can shake. Roman is charming. Mysterious. Infuriatingly flirty. And Juliette? She's simply ... his. When Roman is called back to claim his place in the Montgomery empire, the truth crashes down: Their families are sworn enemies, and Roman's very existence is a threat. Their love isn't just forbidden, it's impossible. Now, every kiss feels like a betrayal. Every stolen moment, a risk. And in a town built on secrets and blood, their passion might just be the most dangerous thing of all"--